Democratic Republic of Congo Rebuilding the Public Service Wage System : Synthesis Note - World Bank (Washington, DC, 2014)
This note focuses on some of the key problems confronting the civil and public service in the Democratic Republic of Congo (DRC), in particular the reform of the wage system and the impact of the decentralization process on civil service reform. It was produced by the World Bank in collaboration with the ministries of public service and budget, as well as with experts of the Cooperation Technique Belge (CTB). The paper is based on an in-depth analysis of the Congolese public service system, published in a separate note, as well as on a series of analytical papers on the decentralization process in DRC, which are available separately. It also incorporates feed-back and comments received during a presentation at the National Forum on Decentralization that was held in Kinshasa, October 3-5, 2007. This analytical paper offers several options aimed at solving the problems that have been identified and discusses in detail the three issues relating to the current reform agenda that are now the key to resolving the fundamental issues below: 1. the impact of the decentralization process on the organization and management of the civil service; 2. the reform of the wage system and, linked to that, the rationalization of the number of civil servants.